Avaliação de germoplasma de milho de germinação precoce em diferentes níveis de nitrogênio e de populações de plantas - Pereira, Antônio Vander; Galvão, José Domingos; Silva, José Carlos; Cardoso, Antônio Américo (Revista Ceres, 2025)
The brachytic-2 maize variety, Piranão, and the first cycle of selection for earliness of germination (Cycle I) of this variety, were evaluated in a field test using a randomized complete block design with two replications. A 2 x 3 x 4 factorial arrangement of treatments was used with two cycles (Cycle I and Original population), three populations densities (40,000; 60,000 and 80,000 plants/ha) and four levels of nitrogen (0; 60; 120 and 180 kg/ha). The following characters were analysed: final stand; plant and ear height; number of ears and ear index; ear production; grain yield; average weight of 50 kernels; and, number of days to silking and to pollen shedding.